2021
DOI: 10.1523/jneurosci.1996-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 in CA1 Area Regulates Spatial Choice Depending on Age

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
5
5
0
Order By: Relevance
“…PSD-95 is a major synaptic protein involved in aging ( Savioz et al, 2014 ; Bustos et al, 2017 ). In this study, hippocampal Psd-95 expression decreased with aging, which has been confirmed in other experiments ( Rogers et al, 2017 ; Cały et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…PSD-95 is a major synaptic protein involved in aging ( Savioz et al, 2014 ; Bustos et al, 2017 ). In this study, hippocampal Psd-95 expression decreased with aging, which has been confirmed in other experiments ( Rogers et al, 2017 ; Cały et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Mice were 2–6 months old at the beginning of the experiments. Only female mice were used in the experiments in the IntelliCages, as males are too aggressive for group housing 55–57 . In other experiments, mice of both sexes were used (sexes were equally distributed between the experimental groups).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were 2-6 months old at the beginning of the experiments. Only female mice were used in the experiments in the IntelliCages, as males are too aggressive for group housing [54][55][56]. In other experiments mice of both sexes were used (sexes were equally distributed between the experimental groups).…”
Section: Animalsmentioning
confidence: 99%